From Tradition to Modernity: The Contemporary Relevance of Islamic Law in Art and Culture - Dewi Kurniawati; Fitri Damayanti; Fatma Merve Prayogo (Islamic Research Publiser, 2024)
This study explores the contemporary relevance of Islamic law in shaping the development of art and culture, highlighting the transition from traditional expressions to modern interpretations. It investigates how the normative principles of Sharia—including ethics, justice, moderation, and spiritual consciousness—interact with artistic creativity and local cultural identities in the modern era. Employing a qualitative-descriptive method supported by literature review and interpretative analysis, this research examines visual art, music, and performance as dynamic media for articulating Islamic values within pluralistic societies. The findings demonstrate that Islamic law, rather than serving merely as a normative restriction, provides an ethical framework that encourages innovation while safeguarding spiritual and moral authenticity. In contemporary practice, this integrative relationship fosters cultural resilience and enables the reinterpretation of Islamic aesthetics in a globalized context. Academically, this study contributes to the discourse on Islamic jurisprudence by offering an interdisciplinary perspective that connects Sharia principles with the philosophy of art and cultural studies. It enriches the understanding of how Islamic legal values can be contextualized to address modern cultural transformation without losing their foundational spirit. Ultimately, the research underscores the need for a balanced paradigm that harmonizes faith-based norms with creative expression, reaffirming Islamic law as a living source of ethical guidance in the realm of art and culture.